Avaliação de adsorventes obtidos a partir de resíduos agroindustriais para a remoção dos inibidores gerados no pré-tratamento da biomassa lignocelulósica - Freitas, Juliana Vieira de (2019)
The pretreatment of lignocellulosic biomass generates phenolic compounds and furaldehydes that inhibit the enzymes and yeast used in the process of hydrolysis of cellulose and alcoholic fermentation. In this context, the aim of this work was to evaluate low-cost adsorbents for the removal of the inhibitors generated in the liquid hot water pretreatment (LHW) of sugarcane bagasse. The materials used to obtain the adsorbents were sugarcane bagasse fly ash and coconut shell charcoal, both agroindustrial residues. Fly ashes from two sugarcane mills were evaluated (named as fly ash A and B), and physical activation of the fly ash B and the coconut shell carbon was also performed. The adsorbents were characterized by pore structure, groups and surface charge, and crystallinity. The activation of the fly ash B resulted in an expressive increase in the surface area and the pore volume of the adsorbent. The structural properties of activated fly ash B showed features less microporous than coconut shell charcoal. All the values of pHpcz of the adsorbents were between 2 and 2.7 for the range of pHs evaluated (2 to 10), except for coconut shell activated carbon that was negative throughout the pH range. Nevertheless, all the adsorbents assessed were effective on the removal of inhibitors and provided the increased glucose in the hydrolysis of cellulose, with gains up to 52%. This positive effect was also observed in the alcoholic fermentation carried out in the presence of the treated liquor, with the coconut shell coconut being very efficient in the removal of the furaldehydes. The results showed that the use of sugarcane bagasse fly ash and the coconut shell activated carbon to remove the inhibitors could increase the efficiency of the enzymatic hydrolysis of the lignocellulosic biomass and the alcoholic fermentation, with performance comparable to the one of commercial activated carbon.